The Positioning of electromagnetic near field hotspots within a resonant cavity for applications in microwave thermal ablation - Young, Graeme Robin (My University, 2022)
The investigation into moving electromagnetic near field hotspots inside a resonant cavity is presented. The investigation is focused on providing an alternative approach to thermal ablation of tumours, by inducing a hotspot over a tumour instead of using an interstitial antenna. The methodology comprised comparing various electromagnetic solvers, verifying the simulation techniques, characterising the resonance within a rectangular resonant cavity, and attempting to control the movement of its hotspots by introducing a phase shift between its sources and modifying their frequency. The effects of dielectric media of the field were also investigated. It was determined that incremental frequency shifts only progressively moved the system’s hotspots between 2.6 and 2.7 GHz and phase shifting only worked between 2.55 and 2.7 GHz when the feeds were on opposite walls. At the system’s eigenfrequencies, no pattern change was evident, indicating that when the chamber was resonating, the field pattern was set. Further, it was determined that the bandwidth of the characteristic modes of the system were very narrow, such that the addition of dielectric material completely altered the resonance of the system and the eigenfrequencies shifted. Therefore, the application of this method to thermal ablation, which requires high precision, accuracy and control, was deemed impractical. Future recommendations include using adjustable cavity geometry and directive microwave sources to design for specific field patterns. Additionally, it is recommended to investigate the validity of the ‘reverse problem’ to create a specific current distribution around the resonant cavity. This is reminiscent of the three-dimensional Green’s Theorem, which would induce the desired hotspot pattern from the surrounding current distribution.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Electrical and Information Engineering, University of the Witwatersrand, Johannesburg, 2021
Keywords: Electromagnetic Near Field Hotspots; Resonant Cavity; Microwave Thermal Ablation; UCTD; SDG-7: Affordable and clean energy